Implementation of Marriage of an Unmarried Girl By Her Biological Father According to Imam Syafi'i (Case Study in Bukit Sofa Village, Subdistrict Siantar Sitalasari Simalungun Regency) - Nurul Ikhwani R*; Ramadani Ramadani (Universitas Syiah Kuala, 2023)
The current phenomenon is that there are many cases where biological fathers marry off extra-marital daughters, one of the factors being that the girl's parents did not inform her that the child was the result of extra-marital affairs (adultery). The madzab imams (Hanafi, Maliki, Hanbali, Shafi'i) differ in their opinions about the law of marrying off a girl by her biological father. The research objective to be achieved in this journal is how the law of marrying off a girl out of wedlock by her biological father according to Imam Shafi'i. Imam Shafi'i argues that the law of marriage of a girl by her biological father is invalid. If a woman and a man marry and a child is born alive and in perfect form before six months, as well as if the child is born after more than six months of marriage but the woman knows that the child existed before the marriage took place, then the child cannot be attributed nasab on behalf of his biological father. The focus of this study is on how Imam Syafi'i's opinion on the law of marrying a girl out of wedlock by her biological father.